(untitled) (The Pakistan Development Review, 2010)
The issue of macroeconomic management in a decentralised set-up is a big question. My part of discussion will get more down into the nuts and bolts and as you see I will unfortunately ask a lot more questions. I think that it is very important that all parties have begin to equip themselves with relatively detailed knowledge of what is likely to occur in the shape and structure of government processes as the devolution of authority in 18th amendment begins to take place. It occurs to me the development stakeholders or the government of Pakistan and the provincial ministries of finance, the Planning Commission and the CCI and potentially others even including the international community. I think these bodes need to know how this devolution can actually occur. What are the actions necessary to develop a transparent budget and an auditable budget, procurements in expenditure processes at the provincial level that were administrated by the federal level in order to avoid macroeconomic management to continue to occur in decentralised set-up. The current arrangement provides as far as I know bulk of resources to be collected and controlled with the federal level. Also there is a significant share of responsibility currently with the federal government. These distributional arrangements will necessarily change as the budgetary regulatory framework for the 18th amendment becomes agreed upon. This regulatory framework is not really in place yet. A regulatory framework would need to be enacted and implemented. This means to me at least that an assessment of pre-18th amendment situation is needed to provide a base line to understand how the new structure will have to be reformed. An assessment perhaps should be done with a review of existing policies or to sort out what were the initial conditions going into 18th amendment. I think as federal and provincial governments are moving towards implementation, at both budgetary and operational levels, a few questions may be needed to be asked. One is how will the new responsibilities assigned to the provinces be financed? What will happen to federal government staff currently engaged in doing all the functions will no longer be with the federal government. How will the human and operational capacity at the provincial government level be developed with a particular emphasis on budgeting expertise and expenditure expertise. If there is going to be control and management at macro level, then there is going to be a tremendous amount of capacity required at the budgeting and expenditure level in the provinces. I think an assessment of the provincial capacity is a good idea.